Long term impact of stressing agents on fermentative hydrogen production: Effect on the hydrogenase flux and population diversity. (April 2016) - Shanmugam, Saravanan R.; Lalman, Jerald A.; Chaganti, Subba Rao; Heath, Daniel D.; Lau, Peter C.K.; Shewa, Wudneh A.
Abstract: In this study, the long term effect of different microbial stressing agents on hydrogen (H2 ) production was examined using repeated batch cultivations. When compared to thermophilic cultures, higher H2 yields were observed in mesophilic cultures receiving repeated glucose addition. Methane production was only observed in control mesophilic cultures receiving repeated 5 glucose additions. Lower hydrogenase evolution specific activity was observed in thermophilic cultures (except alkali-treated cultures) compared to mesophilic cultures. For both mesophilic and thermophilic cultures, the hydrogenase uptake specific activity of the untreated control cultures exhibited higher levels of activity than the pretreated cultures. A flux balance analysis (FBA) showed negligible homoacetogenic flux in mesophilic cultures pretreated with linoleic acid (LA) and loading shock (LS) after successive batch cultivations. The homoacetogenic flux accounted for approximately 98% loss in the H2 yield in untreated mesophilic control cultures. Both homoacetogens ( Eubacterium sp.) and aceticlastic methanogens ( Methanosaeta sp. and Methanosarcina sp.) were abundant in the control cultures. In comparison, Clostridium sp. were dominant in mesophilic stress treated cultures whereas under thermophilic conditions, the dominant microorganisms were Flavobacterium sp., Bacillus sp., Thermoanaerobacter sp., Bacteroides sp., Lactobacillus sp. and Thioalkalivibrio sp. Graphical abstract: Highlights: Elevated levels of methane were detected only in control (untreated) cultures. LA and LS treated mesophilic cultures showed negligible homoacetogenic flux. Control cultures exhibited higher uptake hydrogenase activity. Acetate and butyrate type fermentation was observed in stress treated cultures. Stress treated mesophilic cultures showed high abundance of Clostridium sp.